(untitled) (Nativa, 2024)
This study on the isolation and diagnosis of Acinetobacter baumannii, a bacterium known for its ability to produce protease and antimicrobial agents, has practical implications for the field of microbiology and food safety. A total of 50 samples were collected, including 30 swabs from the floors of various milk factory units and 20 samples from the lands adjacent to the laboratory. The samples were incubated in blood agar, MacConkey, and Mantol salt agar. Twenty bacterial isolates were obtained, including 10 Acinetobacter baumannii, 7 Staphylococcus aureus, and 3 E. coli isolates. All isolates were diagnosed using biochemical tests, API 20 E Kit, and Vitek 2 system. The ability of the isolates to produce the protease enzyme was tested using a skim milk agar medium. Seventeen isolates showed their ability to make the enzyme. Acinetobacter baumannii produced (10) 100%, S. aureus 5 (71.4%), while 2 (66.6%) isolates E. coli. By measuring the diameters of the hydrolyzate on the milk medium, it was found that Acinetobacter baumannii has a high efficiency in producing the protease enzyme with diameters ranging from 15 mm to 45 mm. After the most productive isolate was selected, its diagnosis was confirmed using a molecular technique using 16S rRNA. The crude extract of secondary metabolites was characterized by UV-visible and FTR. The antibacterial effectiveness of the extract was tested using primary and secondary screening protocols. The extract showed high effectiveness, with diameters of inhibition ranging from 20-25 mm against Gram-positive bacteria and 15-23 mm against Gram-negative bacteria. Keywords: protease enzyme; skim milk agar; biochemical test. Isolamento e diagnóstico de Acinetobacter baumannii como produtor de protease e agente antimicrobiano em fábrica de leite ABSTRACT: Este estudo aborda o isolamento e diagnóstico de Acinetobacter baumannii, bactéria conhecida pela sua capacidade de produzir proteases e agentes antimicrobianos, e que tem implicações práticas para o campo da microbiologia e segurança alimentar. Foram coletadas 50 amostras, incluindo 30 amostras de pisos de diversas unidades fabris de leite na região de Babil, Iraque; e 20 amostras foram coletadas em terrenos adjacentes ao laboratório. As amostras foram incubadas em ágar sangue, ágar MacConkey e ágar sal Mantol. Foram obtidos 20 isolados bacterianos, incluindo 10 isolados de Acinetobacter baumannii, 7 de Staphylococcus aureus e 3 de E. coli. Todos os isolados foram diagnosticados por meio de testes bioquímicos, kit API 20E e sistema Vitek 2. A capacidade dos isolados em produzir a enzima protease foi testada utilizando meio ágar leite desnatado. Dezessete isolados mostraram capacidade de produzir a enzima. Acinetobacter baumannii produziu (10) 100%, S. aureus 5 (71,4%), enquanto E. coli produziu 2 (66,6%) isolados. Ao medir os diâmetros do hidrolisado no meio lácteo, constatou-se que Acinetobacter baumannii apresenta alta eficiência na produção da enzima protease, com diâmetros variando de 15 mm a 45 mm. Após a seleção do isolado mais produtivo, seu diagnóstico foi confirmado por técnica molecular utilizando 16S rRNA. O extrato bruto de metabólitos secundários foi caracterizado por UV-visível e FTR. A eficácia antibacteriana do extrato foi testada utilizando protocolos de triagem primária e secundária. O extrato apresentou alta eficácia, com diâmetros de inibição variando de 20-25 mm contra bactérias Gram-positivas e 15-23 mm contra bactérias Gram-negativas. Palavras-chave: enzima protease; ágar leite desnatado; teste bioquímico.